Animal farm eaudiobook - Orwell, George (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2007)
Soon to be an animated film adaptation produced and directed by Andy Serkis George Orwell's classic satire of the Russian Revolution has become an intimate part of our contemporary culture, with its treatment of democratic, fascist, and socialist ideals through an animal fable. The animals of Mr. Jones's Manor Farm are overworked, mistreated, and desperately seeking a reprieve. In their quest to create an idyllic society where justice and equality reign, the animals of Manor Farm revolt against their human rulers, establishing the democratic Animal Farm under the credo, "All Animals Are Created Equal." Out of their cleverness, the pigs—Napoleon, Squealer, and Snowball—emerge as leaders of the new community. In a development of insidious familiarity, the pigs begin to assume ever greater amounts of power, while other animals, especially the faithful horse Boxer, assume more of the work. The climax of the story results in a brutal betrayal, when totalitarian rule is reestablished with the bloodstained postscript to the founding slogan: "But Some Animals Are More Equal than Others." This astonishing allegory, one of the most scathing satires in literary history, remains as fresh and relevant as the day it was published.